Factors Associated with Increased Rates of Post-procedural Stroke or Death following Carotid Artery Stent Placement: A Systematic Review. - Khan, Muhib (Zeenat Qureshi Stroke Research Center, 2014)
BACKGROUND AND PURPOSE: We provide an assessment of clinical, angiographic, and procedure related risk factors associated with stroke and/or death in patients undergoing carotid artery stent placement which will assist in patient stratification and identification of high-stent risk patients. METHODS: A comprehensive search of Medline from January 1st 1996 to December 31st 2011 was performed with key words “carotid artery stenosis”, “ carotid artery stenting”, “carotid artery stent placement”, “death” , ” mortality”, “stroke”, “outcome”, “clinical predictors”, “angiographic predictors”, was performed in various combinations. We independently abstracted data and assessed the quality of the studies. This analysis led to the selection of 71 articles for review. RESULTS: Clinical factors including age≥80 years, symptomatic status, procedure within 2 weeks of symptoms, chronic renal failure, diabetes mellitus, and hemispheric TIA were associated with stroke (ischemic or hemorrhagic) and death within 1 month after carotid artery stent placement. Angiographic factors including left carotid artery intervention, stenosis > 90%, ulcerated and calcified plaques, lesion length > 10mm, thrombus at the site, ostial involvement, predilation without EPD, ICA-CCA angulation > 60%, aortic arch type III, and aortic arch calcification were also associated with 1 month stroke and/or death. Intra-procedural platelet GP IIb/IIIa inhibitors, protamine use, multiple stents, predilatation prior to stent placement were associated with stroke (ischemic or hemorrhagic) and death after carotid artery stent placement. Intraprocedural use of embolic protection devices and stent design (open versus closed cell design) did not demonstrate a consistent relationship with 1 month stroke and/or death. Procedural statin use, and operator and center experience of more than 50 procedures per year were protective for 1 month stroke and/or death. CONCLUSIONS: Our review identified risk factors for stroke, death, and MI within 1 month in patients undergoing carotid artery stent placement. Such information will result in better patient selection for carotid artery stent placement particularly in those who are also candidates for carotid endarterectomy.